Canyon Wall and Floor Debris Deposits in Aeolis Mons, Mars. Issue 2 (27th January 2022) - Hughes, M. N.; Arvidson, R. E.; Dietrich, W. E.; Lamb, M. P.; Catalano, J. G.; Grotzinger, J. P.; Bryk, A. B.
Abstract: Aeolis Mons (informally, Mount Sharp) exhibits a number of canyons, including Gediz and Sakarya Valles. Poorly sorted debris deposits are evident on both canyon floors and connect with debris extending down the walls for canyon segments that cut through sulphate‐bearing strata. On the floor of Gediz Vallis, debris overfills a central channel and merges with a massive debris ridge located at the canyon terminus. One wall‐based debris ridge is evident. In comparison, the floor of Sakarya Vallis exhibits a complex array of debris deposits. Debris deposits on wall segments within Sakarya Vallis are mainly contained within chutes that extend downhill from scarps. Lateral debris ridges are also evident on chute margins. We interpret the debris deposits in the two canyons to be a consequence of one or more late‐stage hydrogeomorphic events that increased the probability of landslides, assembled and channelized debris on the canyon floors, and moved materials down‐canyon. The highly soluble nature of the sulphate‐bearing rocks likely contributed to enhanced debris generation by concurrent aqueous weathering to produce blocky regolith for transport downslope by fluvial activity and landslides, including some landslides that became debris flows. Subsequent wind erosion in Gediz Vallis removed most of the debris deposits within that canyon and partially eroded the deposits within Sakarya Vallis. The enhanced wind erosion within Gediz Vallis was a consequence of the canyon's alignment with prevailing slope winds. Plain Language Summary: Debris deposits on the walls and floors of canyons cut into Mount Sharp are a consequence of late stage precipitation, with ground water infiltration that triggered landslides and debris flows of blocky regolith. This is supported by their morphologies, and by calculations of slope stability in the presence of groundwater. The relatively soluble nature of the sulphate‐bearing strata facilitated chemical weathering to produce material conditioned to fail as landslides. Subsequent wind‐driven erosion degraded many of these features, including differential stripping of wall and floor rocks to generate debris ridges. Key Points: Debris deposits on the walls and floors of canyons cut into Mount Sharp were a consequence of late stage, water‐related events Wind‐driven erosion degraded many of these features, including differential stripping of wall and floor deposits to generate debris ridges